Penerapan Teori Konsumen dalam Menganalisis Pola Konsumsi Masyarakat Modern - Pratiwi Musa, Kartika Septiary (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
This study aims to analyze the theories that explain consumer behavior and the factors that influence it in the context of modern economics and marketing. The background of this research departs from the importance of understanding how individuals make decisions in choosing and buying goods or services in the midst of rapid social changes and digital technology. This study uses a library research method by examining various scientific sources, books, and national and international journals published in the last ten years (2015–2025). The results of the study show that consumer behavior is a multidimensional phenomenon that involves the interaction between economic, psychological, social, cultural, and technological aspects. Theoretically, consumer behavior is explained through cardinal utility theory, ordinal utility theory, and inference curve theory, which describe how consumers seek to maximize satisfaction with resource limitations. In addition, consumer behavior is influenced by internal factors such as motivation, perception, attitude, and lifestyle, as well as external factors such as culture, social groups, family, and economic conditions. The findings of this study confirm that consumer behavior in the digital age is not only driven by economic rationality, but also by symbolic value, emotions, and awareness of sustainability. This research is still conceptual, so further empirical studies are needed to test the application of consumer behavior theory in different industry contexts. The results of this study are expected to contribute to the development of management and marketing science, as well as become the basis for companies to design adaptive, ethical, and sustainable marketing strategies.